2010
DOI: 10.1111/j.1365-2311.2009.01136.x
|View full text |Cite
|
Sign up to set email alerts
|

Intranidal mating, gyne polymorphism, polygyny, and supercoloniality as factors for sympatric and parapatric speciation in ants

Abstract: Abstract. 1. The syndrome of intranidal mating, morpho-ethological gyne polymorphism, and polygyny is found in less than 5% of European ant species, but is considered as an important precondition for sympatric and parapatric speciation.2. This idea is discussed in three cases that represent example of evolution below the species level: (1) the polygynous-polydomous form of Lasius turcicus as a model of how speciation of the supercolonial Lasius neglectus could have taken place; (2) the microgyne form of Myrmic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 46 publications
1
17
0
1
Order By: Relevance
“…Polygyny, in particular, presents an opportunity for one queen to reproductively exploit the other queen(s) and can lead to the evolution of intraspecific parasitism (Buschinger 1986;Seifert 2010;. Interestingly, every host and parasite species of fungus-growing ants that has been investigated so far is at least facultatively polygynous (Della Lucia and Vilela 1986;Delabie 1989;Bekkevold et al 1999;Bekkevold and Boomsma 2000;Diehl et al 2001;De Souza et al 2004;Rabeling et al 2007b;Rabeling and Bacci 2010), which supports the hypothesis that the evolutionary origin of social parasitism is contingent on the presence of polygyny in a given species.…”
Section: Mating Behavior and Reproductive Strategysupporting
confidence: 51%
“…Polygyny, in particular, presents an opportunity for one queen to reproductively exploit the other queen(s) and can lead to the evolution of intraspecific parasitism (Buschinger 1986;Seifert 2010;. Interestingly, every host and parasite species of fungus-growing ants that has been investigated so far is at least facultatively polygynous (Della Lucia and Vilela 1986;Delabie 1989;Bekkevold et al 1999;Bekkevold and Boomsma 2000;Diehl et al 2001;De Souza et al 2004;Rabeling et al 2007b;Rabeling and Bacci 2010), which supports the hypothesis that the evolutionary origin of social parasitism is contingent on the presence of polygyny in a given species.…”
Section: Mating Behavior and Reproductive Strategysupporting
confidence: 51%
“…If gene flow within taxon A (or B) is limited, for example in a patchy environment, a second outcome of reinforcement may be the evolution of reproductive traits in overlap populations that are so divergent from those outside the area of contact that individuals with the alternative trait types are less likely to reproduce (Howard, 1993; see also reviews, discussion, and references therein by Pfennig & Pfennig, 2009, 2010Ortiz-Barrientos et al, 2009;Hoskin & Higgie, 2010). Consequently, this can lead to the initiation of reproductive isolation between sympatric and allopatric populations of taxon A (or B), which can ultimately lead to speciation (Howard, 1993;Pfennig & Pfennig, 2009, 2010Ortiz-Barrientos et al, 2009;Hoskin & Higgie, 2010; for theoretical treatments see Pfennig & Ryan, 2006;McPeek & Gavrilets, 2006). For example, Jaenike et al (2006) showed that, between two sympatric species of Drosophila, strong hybrid inviability not only selected for discrimination against heterospecifics but also, as a side product, led to discrimination against conspecifics from allopatric populations.…”
Section: Consequences Of Reinforcementmentioning
confidence: 99%
“…Trade-offs in fitness between assortative mating and sexual selection within populations may enhance the divergence between populations (e.g. Pfennig & Pfennig, 2005; for further discussion, see Pfennig & Pfennig, 2009, 2010Ortiz-Barrientos et al, 2009;Hoskin & Higgie, 2010). These trade-offs may be emphasized when a stepwise change in environmental conditions coincides with the boundary of the region of range overlap.…”
Section: Consequences Of Reinforcementmentioning
confidence: 99%
“…This result suggests that the clusters are not completely distinct. It may be attributed to long-distance dispersal of the ghost ant that frequently occurs due to human activities (Seifert, 2010). Therefore, newly introduced populations may mix with earlier arrivals to form a single more genetically diverse unicolonial society, thus promoting gene flow at large scales among island and mainland populations.…”
Section: Population Genetic Structurementioning
confidence: 99%